Bargaining for trade: When exporting becomes detrimental for female wages - Daniel Halvarsson; Olga Lark; Patrik Tingvall; Josefin Videnord (Lund University, School of Economics and Management, Department of Economics, 2022)
In this paper we study the link between globalization of firms and gender inequality. Specifically, we examine how the need for interpersonal contacts in trade and gender-specific differences in negotiations are related to the gender wage gap. Our key finding is that export of goods that are intensive in interpersonal contacts widens the gender wage gap. The effect is robust across various specifications and is most pronounced for domestic exporting firms, which do not trade within multinational corporations but with external foreign partners, where the contracting problem is most distinct. We ascribe this result to a male comparative advantage in bargaining.
Keywords: J16; J31; F16; F66; 330; Export; Gender wage gap; Gender inequality; Contract intensity; Interpersonal contacts; International trade